2008
DOI: 10.3746/jkfn.2008.37.10.1258
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Radish Leaves Powder on the Gastrointestinal Function and Fecal Triglyceride, and Sterol Excretion in Rats Fed a Hypercholesterolemic Diet

Abstract: The current study examined the effects of radish leaves powder on the excretion of fecal triglyceride, and sterol and hepatic UDP-glucuronyl transferase (UDPGT) activity in rats fed hypercholesterolemic diet. Male Sprague-Dawley rats weighing 100±10 g were randomly assigned to normal control group (N group), normal diet with 5% radish leaves powder supplemented group (NR) and hypercholesterolemic groups, which were subdivided into radish leaves powder free diet group (HC) and 2.5% (HRL), 5% (HRM), and 10% (HRH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 16 publications
1
2
0
1
Order By: Relevance
“…The findings of the current study agree with the result of Jang et al (27) in which the feces, total lipid, total cholesterol, and TG contents were increased by feeding with untreated radish leaves, and the physiological effects of dietary fiber and flavonoids were reported by Kang et al (2) The enzymatic treatment of radish leaves increases the useful dietary fiber contents and the previous results can indicate that enzyme-treated radish leaves are more effective in increasing water-SDF levels than non enzyme-treated radish leaves. The findings of the current study also agree with the result of Yim et al (36) where glucomannan, an SDF, reduced weight while significantly decreasing dry weight water and fat contents, helping excretion with no side effects.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The findings of the current study agree with the result of Jang et al (27) in which the feces, total lipid, total cholesterol, and TG contents were increased by feeding with untreated radish leaves, and the physiological effects of dietary fiber and flavonoids were reported by Kang et al (2) The enzymatic treatment of radish leaves increases the useful dietary fiber contents and the previous results can indicate that enzyme-treated radish leaves are more effective in increasing water-SDF levels than non enzyme-treated radish leaves. The findings of the current study also agree with the result of Yim et al (36) where glucomannan, an SDF, reduced weight while significantly decreasing dry weight water and fat contents, helping excretion with no side effects.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, SDF content of enzyme-treated radish leaves is greater than untreated radish leaves. Jang et al (27) reported that ginger contained nearly 6.0% crude fiber, which increased to 15.7% after zymolysis. Radish leaves were also found to have higher levels of IDF and SDF through enzyme treatment, indicating that TDF content increased.…”
Section: Discussionmentioning
confidence: 99%
“…Such increases were caused by dietary fiber and flavonoids in the plants (40). Notably, quercetin, which is a kind of flavonoid, decreases the serum cholesterol and LDL-C level by suppressing the activity of the HMG-Co A reductase within liver tissue and controlling the formation of cholesterol in body (41).…”
Section: Fecal Lipid Levelsmentioning
confidence: 99%
“…Клетчатка устраняет запоры и прочищает ЖКТ, вбирая в себя токсичные элементы. Кстати, в одном из исследований на крысах корейские учёные заметили, что не только сам корнеплод, но и листья растения способствуют нормализации работы желудка и кишечника [9] . Помимо этого, редис стимулирует выработку желчи, которая также необходима для процесса пищеварения.…”
Section: лечебные свойстваunclassified

Редис (лат. radix)

Елисеева Татьяна,
Тарантул Алёна
2019
ЖЗПД